King of Kings Ardashir I as Xerxes in the Late Antique Latin Sources - Sólyom, Márk (Acta Classica Universitatis Scientiarum Debreceniensis, 2022)
The last ruler of the Severan dynasty, Emperor Severus Alexander had to face an entirely new threat in Mesopotamia, because in 224 AD the Parthian royal house of the Arsacids, which had ruled in the East for nearly half a millennium, was dethroned by the Neo-Persian Sasanian dynasty and the new rulers of Persia were extremely hostile to the Roman Empire. The vast majority of the late antique Latin sources (Aurelius Victor, Eutropius, Festus, Jerome, Orosius, Cassiodorus, Iordanes) call the first Sasanian monarch, Ardashir I (reigned 224–241 AD), who was at war with Rome between 231 and 233 AD, Xerxes, although the Greek equivalent of the Middle Persian name Ardashir is Artaxerxes, as used by the Greek sources. In the Latin textual tradition we can find the correct Greek name of Ardashir only in the Historia Augusta. The paper seeks answers to the question of why Ardashir was usually called Xerxes by late antique Latin sources.